The Charismatic City and the Public Resurgence of Religion: A Pentecostal Social Ethics of Cosmopolitan Urban Life - Wariboko, Nimi (Christianity and Renewal - Interdisciplinary Studies, 2014)
Two powerful and interrelated transnational cultural expressions mark our epoch, Charismatic spirituality and global city. This book demonstrates how these two forces can be used to inform ethical design of cities and their common social lives to best support human flourishing, spirituality, and social and ecological wellbeing of their residents